Chemistry : atoms first. - Open Textbook Library; OpenStax College; BC Open Textbook Project; BCcampus (OpenStax College, Rice University, 2016)
"Chemistry: Atoms First is a peer-reviewed, openly licensed introductory textbook produced through a collaborative publishing partnership between OpenStax and the University of Connecticut and UConn Undergraduate Student Government Association. This title is an adaptation of the OpenStax Chemistry text and covers scope and sequence requirements of the two-semester general chemistry course. Reordered to fit an atoms first approach, this title introduces atomic and molecular structure much earlier than the traditional approach, delaying the introduction of more abstract material so students have time to acclimate to the study of chemistry. Chemistry: Atoms First also provides a basis for understanding the application of quantitative principles to the chemistry that underlies the entire course."--Open Textbook Library.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Includes index.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online version, revision: CAF-2016-000(07/16)-BKB; Title from PDF (viewed on August 31, 2016)
Keywords: Chemistry -- Textbooks; Chemistry; Textbooks